Fabrication of three-dimensional photonic crystals with tunable photonic properties by biotemplating - Van Opdenbosch, Daniel; Johannes, Maren; Wu, Xia; Fabritius, Helge; Zollfrank, Cordt (Photonics and Nanostructures-Fundamentals and Applications, 2012)
Photonic crystals with tunable D-surface structures for possible high-temperature gas- and temperature-sensing applications were prepared by a biotemplating method. This included infiltrating colored scales of the beetle Entimus imperialis with an organopolysiloxane mixture followed by simultaneous combustion of the template and calcination of the cured organopolysiloxane. A high-yield inorganic silica-based replica of the original structure was obtained, which is capable of withstanding temperatures up to 600 °C. Light- and scanning electron microscopy combined with focused ion beam milling showed a precise replication of the whole scales and their internal D-surface structure. Fourier-transform infrared spectroscopy and X-ray diffraction analysis confirmed the complete curing of the organopolysiloxanes and their transformation into amorphous silica during calcination. The dielectric constant of the manufactured materials determined by Abbé refractometry was ε = 2.3180 and used to perform band structure calculations utilizing the plane wave expansion method. By changing the chain length and degree of crosslinking of the organopolysiloxane precursor mixture, the lattice parameters and filling factors, and therefore the photonic properties of the replicas, could be tuned. © 2012 Elsevier B.V. All rights reserved.
LFT Import::2019-07-29 (1810)
Keywords: Biotemplating; D-surface; Inorganic; Photonic; Sensing application; Tunable